Physiological adaptations and anatomical distortions occurred at some respiratory system physical & architectural components in the frogs affected by the nasty environment of Karun river - Hassan A-S, U. (Al-Qadisiyah Journal of Pure Science, 2018)
The current search results revealed the presence of anatomical changes on the architectural levels in the noses of Iranian frogs affected by the polluted environment of Karun river which led to subsequent events of physiological adaptations subjected to biophysical equations previously approved in order to save the life of internal stability (homeostasis) and life of these animals that were affected by the polluted water in the Karun River along the Iraqi border. Results showed that radii slots of frog's noses widened by 0.068-0.07 mm and almost step-by-step along this short noses. On the other hand the physiological adaptations of these animals focused on increasing the volume and pressure of gases within the fading waterways in order to balance the ratio of oxygen deficient environment in the contaminated river with change in the values of the constants of equations related to this case. Conclusion of this research proves that Iranian frogs that are internationally unique were suffers from anatomical defects that had, in turn, contributed to a somewhat equivalent lack of oxygen needed for vital events within the studied river environment and this will lead to similar studies in humans and other organisms that affected by the polluted environment of rivers and what may happen to them regarding the conformations and modifications from these pollutants.